Membangun Inovasi di Era Digital: Pengaruh Pembelajaran Digital terhadap Perilaku Kerja Karyawan Magang melalui Kesiapan untuk Berubah - Arum Etikariena; Puspita Buana Amartya Dewi (Psychopolytan : Jurnal Psikologi, 2024)
Technological developments have made the use of digital technology in everyday life, including the implementation of tasks in organizations, making competition for companies to innovate even tighter. Apprentices as prospective workers in the future are expected to have innovative work behavior so that innovation in the company becomes easier. This research aims to determine the influence of digital learning orientation on innovative work behavior which is mediated by readiness to change. Data were obtained with convinience sampling, from interns who live in Indonesia (N = 285). The participants have aged between 18-23 years (M =21. 35; SD =3.40). There are three measuring tools used in this research, the nine-item innovative work behavior scale, the fifteen-item digital learning orientation scale and the readiness for change scale consists of fourteen items. Analysis using Hayes' simple mediation analysis technique using PROCESS version 4.0. The research results show that readiness to change is partial mediated the influence of digital learning orientation on apprentices' innovative work behavior. This study can provide insights for interns to better prepare themselves for the challenges they will face when entering the workforce. Additionally, for educational institutions or campuses, the findings of this study can serve as a consideration in designing curricula that equip students to face these challenges.